Estudo do comportamento mecânico do fosfogesso hemi-hidratado - Santos, Thiago Lopes dos (2016)
The phosphogypsum is generated from the production of the phosphogypsum acid in the fertilizer industry and phosphate fertilizers. Studies show that phosphogypsum can be applied in areas such as civil construction, the cement industry and agricultural sector. However this is used in low quantities. In pavements construction, is the phosphogypsum can be used and many studies have been taken at the Universidade Federal de Goias (UFG). In this context, the objective of this work was to study the hemihydrate gypsum (HH) in mixtures with soil, cement and lime, in order to facilitate and expand its use in paving. The heat treatment of dehydrate gypsum (DH) was carried out in the Goias state, thus obtaining the phosphogypsum (HH). Three mixtures were studied: Mixture S+HH (50% soil, 50% phosphogypsum HH); Mixture S+HH+CIM (50% soil, 41% phosphogypsum HH and 9% cement) and Mixture S+HH+CAL (50% soil, 44% phosphogypsum HH and 6% lime). Characterisation tests were conducted (utilising traditional methodology and the MCT methodology) and mechanical strength tests (unconfined compressive strength – UCS and resilient modulus – RM) to obtain parameters for use in paving. Deformability tests were also carried out, through consolidation tests, to evaluate the stabilisation of deformation of phosphogypsum HH over time, and stability when subjected to a load in the saturated and unsaturated conditions. In was studied the effect of bad weather conditions on the samples through resistance tests to the simple compression in samples exposed to the elements for up to 180 days. Scanning electron microscopy tests (SEM) were performed to understand the micro structural behaviour. In the samples that contained phosphogypsum HH there was greater UCS than the samples that contained only soil and mixtures with the same phosphogypsum DH proportions. The mixture S+HH+CIM obtained greater resistance and the mixtures S+HH+CAL and S+HH showed similar results, making the use of lime unnecessary. The RM, like the UCS showed better results for the mixture S+HH+CIM. With regards to deformability, mixture S+HH+CIM showed lower deformations than the other mixtures and a tendency towards stabilisation in unsaturated condition, contrary to mixtures S+HH and S+HH+CAL. During the evaluation of the effect of bad weather, mixture S+HH+CIM showed a 15% reduction of resistance through time, 25% resistance reduction for mixture S+HH+CAL and 50% for mixture S+HH. However, these values are still superior to mixtures using phosphogypsum DH used in past researches. When the microstructure of the samples were evaluated, they showed phosphogypsum DH transformed into HH; this behaviour was more consistent in the mixture S+HH. Finally it can be concluded that mixtures containing phosphogypsum HH are viable application in paving base layers.